THE MEDIATING ROLE OF PSYCHOLOGICAL SAFETY IN THE RELATIONSHIP BETWEEN EMPOWERING LEADERSHIP AND EMPLOYEE INNOVATIVE BEHAVIOR - Tuo, Wenjian; Zhou, Wenjie; Hua, Guowei; Zhang, Yajun; Li, Jian (Chinese Journal of Social Science and Management, 2026)
Purpose: This study systematically analyzed and explained how empowering leadership significantly enhances employees’ innovative behavior by fostering psychological safety. Study Design/Methodology/Approach: This study combines literature analysis and quantitative analysis of questionnaire data. SPSS is used as the data analysis tool, and multiple regression analysis is applied to analyze scientific data, including descriptive statistics, reliability, and validity analyses, and the Common Method Bias (CMB) test, and tests of direct and mediating eﬀects to support the research theme. Findings: Empowering leadership can indirectly facilitate employees’ innovative behavior by fostering a safe, open working environment. The R² of the mediating eﬀect model was 0.4827 with an F-value of 35.46. The indirect eﬀect value of psychological safety was 0.2984 (95% CI = [0.2030, 0.4024]). The results verified the hypothesis that psychological safety acts as a mediating role between empowering leadership and employees’ innovative behaviors. Originality/Value: This study confirmed the mediating role of psychological safety in the relationship between empowering leadership and employees’ innovative behavior. The research focused on the information technology industry, providing important practical guidance for this rapidly developing sector. Fostering employees’ psychological safety is an unavoidable task for organizations.